The Effects of Cultural Differences on Post - Acquisition Success for Multinational Firms (Journal of Organizational Psychology, 2022)
The aim of this article is to provide a comprehensive review on national culture, organizational culture, and international mergers and acquisitions. Previous research investigating national culture and mergers and acquisitions has focused more on the transferring processes. This article focuses on post-acquisition performance and utilizes two case studies to demonstrate how national culture and organizational culture impact on post-acquisition performance for multinational companies. Hofstede’s four-dimension theory in national culture is used to compare and contrast those different national cultures. Two case studies are the Yahoo-Kimo acquisition and Benq-Siemens acquisition. Therefore, three different countries are involved. They are Taiwan, the US, and Germany. The author also provides suggestions for future research.
Keywords: organizational psychology; cultural differences; organizational culture; national culture; acquisitions